Celtic harmony : a wonderful musical journey through Ireland, Scotland and Wales for relaxation and meditation - Evans, Gomer Edwin (Neptun Media, 2012)
Evans invites you to a relaxing journey through Celtic countries. His music creates an authentic atmosphere and takes you deep into the heart of the Celtic mysteries. Rest your mind and enjoy these pleasant melodies that help harmonize your body, mind and soul.